Pengaruh Promosi, Life Style, dan Brand Image Terhadap Keputusan Pembelian Produk Viva Kosmetik di Kota Batam - Harahap, Sarifa; Winda Evyanto (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of promotion, lifestyle, and brand image on the purchasing decisions of Viva Cosmetics products in Batam City. The rapid growth of the cosmetic industry has intensified competition, leading to a decline in consumer interest in Viva Cosmetics. Less appealing promotional strategies, the shift toward modern consumer lifestyles, and an outdated brand image are considered major factors affecting purchasing decisions. This research applies a quantitative method with data collected through questionnaires distributed to cosmetic consumers in Batam City. The data were analyzed using multiple linear regression with SPSS software. The findings indicate that promotion and brand image have a positive and significant effect on purchasing decisions, while lifestyle shows a negative effect. Simultaneously, all three variables significantly influence the purchasing decisions of Viva Cosmetics products. The results of this study are expected to provide insights for Viva Cosmetics in improving its marketing strategies, particularly by enhancing promotional activities and strengthening its brand image to align with modern consumer lifestyles.